Simultaneous minimally invasive surgery for pectus excavatum and recurrent pneumothorax - BOSTANCI, KORKUT (OXFORD UNIV PRESS, 2012)
A 19-year old male who had a pectus excavatum deformity and recurrent primary spontaneous pneumothorax was admitted to our clinic. An intervention simultaneously combining a videothoracoscopic apical wedge resection and minimally invasive repair of the pectus excavatum deformity was successfully performed.
Keywords: Chest wall; Minimally invasive surgery; Pectus excavatum; Pneumothorax